Predicting Learning Anxiety Through Adversity Quotient - Shella Nurfadillah; Fijriani Fijriani; Rizki Akhri Januar (Asosiasi Asesmen Pendidikan (AAP), 2024)
The aim of this study is to determine whether there is an effect of adversity quotient on learning anxiety and to describe the adversity quotient and learning anxiety of students. This research employs a quantitative approach. The population and sample of this study are all 227 students of the 11th-grade at SMA Budhi Warman 1 East Jakarta. Data on adversity quotient and learning anxiety were collected through two questionnaires, the adversity quotient instrument developed from Paul G. Stoltz's theory (2005) consisting of 23 items, and the learning anxiety instrument developed from Allen J. Ottens’s theory (1991) consisting of 21 items. The data were analyzed using SPSS software with a linear regression technique. The findings of this study indicate a significant effect of adversity quotient (X) on learning anxiety (Y), with the adversity quotient contributing 30.2% to learning anxiety. Additionally, the regression coefficient is negative, indicating that an increase in adversity quotient leads to a decrease in learning anxiety.